The Impact of Toxic Ball Warming on Children's Engagement in Volleyball at SMA Negeri 2 Semarang - Hidayatulloh, Farijan (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This study seeks to investigate the impact of a toxic ball warm-up on students' enthusiasm for playing volleyball at SMA Negeri 2 Semarang. Materials and Methods. The employed research methodology was quasi-experimental, utilizing a pretest-posttest design. The research subjects consisted of 36 students selected randomly. Results. The findings indicated that the introduction of the poison ball warm-up markedly enhanced students' enthusiasm for playing volleyball. Prior to the deployment, merely 40% of pupils shown great curiosity, however subsequent to the implementation, this percentage rose to 75%. Moreover, students' engagement in volleyball activities rose from 50% to 85%, while fundamental volleyball abilities, including serving, passing, and smashing, improved from 60% to 80%. Conclusion. This study indicates that the poison ball warm-up effectively enhances students' enthusiasm and skills in volleyball. Consequently, it is advisable to implement this strategy consistently in sports instruction to enhance students' motivation and abilities.